(3OjhGf GdTQja GdQVjs - (3eMeO Hf GdMSjf Hf ehSi GdYdhj GdMSjfj GdehShj, GdTQja GdQVj , CHh GdMSf,J (B406 (3g` s ((3eMeO QDha GdHGabi s)
(3ChdgG (B:s
(3Cperd ef eKGfjgG agPG ebjdgG hgPG eZGfj OQGge hWdhdgG s
(3BNQgG (B:s
(3hQCj Cf dG fLGI dg aeVi jHZj GdfLGI ZOG s
(3fSNI NGeSI eNJGQGJ ef GdOjhGfs
(3hQOJ CjVkG JMJ Qbe (B2191(3, (B2244(3, (B70(3, (B725s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B261s
Keywords: (3GdCOHs